2017
DOI: 10.3892/etm.2017.5522
|View full text |Cite
|
Sign up to set email alerts
|

miR‑221 inhibits autophagy and targets TP53INP1 in colorectal cancer cells

Abstract: Abstract. Colorectal cancer (CRC) is the third most common cancer and the fourth leading cause of cancer-associated mortalities worldwide. MicroRNAs (miRNAs/miRs) serve important roles in tumor development, progression and metastasis. miR-221 has been reported to modulate proliferation, apoptosis, cell cycle distribution and cell migration in a variety of cancers. However, the function of miR-221 in the autophagy of cancer is unclear. In the present study, the role of miR-221 in the autophagy of CRC cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Table 4). The p53-inducible protein 1 (TP53INP1) promotes autophagy by interacting with autophagosome-localized autophagyrelated protein family (ATG) proteins (49). Even though ATG4D expression was slightly (∼2-fold) sustained by 4 hpi and throughout the infection period, TP53INP1 was repressed by 2.6-fold at 8 hpi ( Supplementary Table 4).…”
Section: Intracellular Transportmentioning
confidence: 99%
“…Table 4). The p53-inducible protein 1 (TP53INP1) promotes autophagy by interacting with autophagosome-localized autophagyrelated protein family (ATG) proteins (49). Even though ATG4D expression was slightly (∼2-fold) sustained by 4 hpi and throughout the infection period, TP53INP1 was repressed by 2.6-fold at 8 hpi ( Supplementary Table 4).…”
Section: Intracellular Transportmentioning
confidence: 99%
“…Dysregulation of miRNAs is involved in many cancers, and some miRNAs function as tumor suppressors or oncogenes. 16 , 17 miR-221 has been identified as an oncogene in many types of cancers, including colorectal cancer, 18 breast cancer, 19 and osteosarcoma. 20 Bioinformatics analysis found that miR-221 was a target of GAS5.…”
Section: Introductionmentioning
confidence: 99%
“…By antagonizing TP53INP1 and Yes1 associated transcriptional regulator (YAP1), upregulated miR-200a enhances drug resistance in breast cancer (24). In colorectal cancer, miR-221 promoted cell proliferation via the inhibition of autophagy and targeted TP53INP1 (25). In this study, TP53INP1 was predicted and confirmed to be a target of miR-8055.…”
Section: Discussionmentioning
confidence: 62%